2009
DOI: 10.1177/1740774509105222
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and political challenges in North America's first randomized controlled trial of heroin-assisted treatment for severe heroin addiction: Rationale and design of the NAOMI study

Abstract: Background-Heroin addiction is a chronic relapsing disease, best treated with opioid-agonist substitution therapy such as methadone maintenance. However, a subset of the most severely affected individuals do not benefit sufficiently from this treatment. The North American Opiate Medication Initiative (NAOMI) is a randomized clinical trial (RCT) to evaluate the hypothesis that pharmaceutical-grade heroin, diacetylmorphine (DAM) is more effective in retaining patients and improving their outcomes than Methadone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…The main difference with other trials was the 12-month duration of HAT, which was introduced for legal and political reasons. The only other trial with a predetermined end of HAT was the Canadian study, in which street heroin use rose in the experimental group between the 9- and 12-month assessments [5,34]. In the Dutch trial, after 12 months, an interruption of HAT for 2 months also had a negative impact: 82% of the participants who were completers and responders deteriorated substantially [6].…”
Section: Discussionmentioning
confidence: 99%
“…The main difference with other trials was the 12-month duration of HAT, which was introduced for legal and political reasons. The only other trial with a predetermined end of HAT was the Canadian study, in which street heroin use rose in the experimental group between the 9- and 12-month assessments [5,34]. In the Dutch trial, after 12 months, an interruption of HAT for 2 months also had a negative impact: 82% of the participants who were completers and responders deteriorated substantially [6].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed inclusion and exclusion criteria and baseline characteristics of the study participants have been published previously. 23,28 In brief, at baseline, the study participants were 25 years or older, with regular opioid injection, a minimum five-year history of opioid use, and at least two previous attempts at substitution treatment for opioid dependence. The average age of the participants was 39.7 years, and 61.4% were men.…”
Section: Model Designmentioning
confidence: 99%
“…The baseline prevalence of HIV infection was 9.6% and of hepatitis C virus infection 62.9%. 23 Health states in our model 29 included treatment (diacetylmorphine or methadone maintenance treatment), relapse (defined by opioid use outside of treatment), abstinence from opioids and death. Patients in the model belonged to one of two cohorts (diacetylmorphine or methadone maintenance treatment), and all patients entered the model in a treatment state, which was assumed to be their third attempt at treatment.…”
Section: Model Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The North American Opiate Medication Initiative (NAOMI) trial in Canada showed heroin-assisted maintenance of "refractory" opioid dependence to have better outcomes compared to methadone treatment in terms of retention in treatment and clinical response [79,80]. An important caveat is that all those in the trial had previously failed methadone treatment, and so those randomized to methadone were, in effect, randomized to a treatment previously found ineffective.…”
Section: Other Pharmacotherapy Paradigmsmentioning
confidence: 99%